Does fiscal decentralization have a differentiated effect on structural economic transformation in Africa? - Chretien, Nzomo Tchuenta Joseph; Lambert, Nguena Christian; Radler, Romaine Doline Ngo Ngueda Epse; Ibrahim, Ngouhouo (Asian Journal of Economic Modelling, 2025)
The main objective of this article was to explore the influence or effects of fiscal decentralization on economic structural changes in developing countries based on a global indicator presented by twelve different variables measuring economic sustainable development. The current study aims to survey the weakness of the old paradigm of structural economic transformation, which for decades promoted the importation of foreign technology and capital, the prioritization of heavy industry, and the neglect of both regional population centers and small businesses. To attain this goal, we apply different methods, such as Driscoll and Kraay, GMM, and Lewbel 2SLS, to explore the socio-cultural mechanisms shaping development. The results highlight that fiscal decentralization can indeed foster structural transformation across the continent, especially in North, West, Central, and Southern Africa. Yet, fiscal decentralization slowed the rate of structural economic transformation in East Africa. The study emphasizes the importance of establishing transparent revenue collection systems and ensuring efficient resource allocation within local structures. Implementing such measures is crucial in leveraging fiscal decentralization as a driving force for promoting structural economic transformation throughout the African continent.